The Influence of Religiosity, Attachment to God and Education Level on Mental Health of Youth in Gereja Kristen Jawi Wetan (GKJW) Rungkut Surabaya in Indonesia - Daniel, Dirtilan; Juanda, Juanda; Lambertus, Frederich Oscar (Theological Journal Kerugma, 2024)
The purpose of this study was to assess the mental health conditions influences by religiosity, education level and attachment to God on the mental health of youth in GKJW Rungkut, Surabaya. Data were collected using a questionnaire administered to youth in GKJW Rungkut, Surabaya, aged between 16 and 35 years. The sample comprised 120 respondents. The questionnaire used a Likert scale (1-5), and statistical analysis was conducted using Warp-PLS. The results indicate that the levels of religiosity and mental health among the youth in GKJW Rungkut, Surabaya, are significant. However, aspects such as anxiety and low self-esteem are still at a moderate level. This suggests that a significant level of religiosity alone has not been able to fully address anxiety and low self-esteem. Statistical testing revealed that religiosity, education level, and attachment to God have a simultaneous influence on the mental health of the youth in GKJW Rungkut. The research model demonstrated adequate predictive relevance (Q² > 0), indicating that it can be used for further research.